GUIDING LIGHTS: NAVIGATING PARENTING STYLES IN CHILDREN’S MORAL DEVELOPMENT - Syazwani binti Husin; Nurulafzan binti Sa’ari; Wan Nur Ainna Waheda binti Rozali (Journal of Islamic, Social, Economics and Development, 2023)
This paper will examine the role that parenting styles play in a child's moral development. Parenting styles give an impact on children’s moral development in their daily life. Based on theory by Diana Baumrind’s parenting style which are highlighted four types of parenting style, authoritative, authoritarian, permissive and neglectful have an impact on moral development. The concept paper discusses about the issues in parenting style that affect children’s moral development, especially for young children who can already distinguish between right and wrong actions or choices in their life. The methodology used in this paper is content analysis and to get the data, researcher used document analysis. Issues in parenting styles in children’s moral development found which are cultural influences, cross-cultural comparison of parenting styles, techonology and family interaction, dual-earner family challenges, pressure and stress and equal roles and reversals. The recommendations which emphasize the importance of love, intimacy, support and encouragement have been put forth and thoroughly explored, strengthening the argument about the significance of parenting styles in growing children.